The Involvement of PPARs in the Selective Regulation of Brain CYP2D by Growth Hormone. (21st May 2018) - Zhang, Furong; Li, Jie; Na, Shufang; Wu, Juan; Yang, Zheqiong; Xie, Xianfei; Wan, Yu; Li, Ke; Yue, Jiang
Highlights: The inhibition of cerebellar CYP2D induces the impairment of memory and emotion. GH selectively increases brain CYP2D via tissue-specific regulation of PPARγ. CYP2D gene is positively regulated by PPARγ and negatively regulated by PPARα. GH may affect memory and emotion in patients with GH treatment via brain CYP2D. Abstract: Brain CYP2D is responsible for the synthesis of endogenous neurotransmitters such as dopamine and serotonin. This study is to investigate the effects of cerebral CYP2D on mouse behavior and the mechanism whereby growth hormone regulates brain CYP2D. The inhibition of cerebellar CYP2D significantly affected the spatial learning and exploratory behavior of mice. CYP2D expression was lower in the brain in GHR−/− mice than that in WT mice; however, hepatic CYP2D levels were similar. Brain PPARα expression in male GHR−/− mice were markedly higher than those in WT mice, while brain PPARγ levels were decreased or unchanged in different regions. However, both hepatic PPARα and PPARγ in male GHR−/− mice were markedly higher than those in WT mice. Pulsatile GH decreased the PPARα mRNA level and increased the mRNA levels of CYP2D6 and PPARγ in SH-SY5Y cells. A luciferase assay showed that PPARγ activated the CYP2D6 gene promoter while PPARα inhibited its function. Pulsatile GH decreased the binding of PPARα to the CYP2D6 promoter by 40% and promoted the binding of PPARγ to the CYP2D6 promoter by approximately 60%. The male GH secretory pattern altered PPAR expression and the binding of PPARs to the CYP2D promoter, leading to the elevation of brain CYP2D in a tissue-specific manner. Growth hormone may alter the learning and memory functions in patients receiving GH replacement therapy via brain CYP2D.